In vivo toxicity assessment of the probiotic Bacillus amyloliquefaciens HTI-19 isolated from stingless bee (Heterotrigona itama) honey - Zulkhairi Amin, Fatin Aina; Shafiq Cheng, Mohamad Zulhafiz; Sabri, Suriana; Ismail, Norsharina; Chan, Kim Wei; Mohd Esa, Norhaizan; Mohd Lila, Mohd Azmi; Nur-Fazila, Saulol Hamid; Khalifa, Shaden A. M.; El-Seedi, Hesham R.; Zawawi, Norhasnida (Multidisciplinary Digital Publishing Institute, 2023)
This study evaluated the acute and sub-acute toxicity of B. amyloliquefaciens HTI-19 (isolated from stingless bee honey) in female Sprague Dawley rats. In an acute toxicity study, the rats received a low dosage (1 × 109 CFU·mL−1 ), medium dosage (3 × 109 CFU·mL−1 ), or high dosage (1 × 1010 CFU·mL−1 ) of B. amyloliquefaciens HTI-19 daily orally by syringe-feeding for 14 days. For the subacute toxicity study, rats received a low dosage (1 × 109 CFU·mL−1 ) or a high dosage (1 × 1010 CFU·mL−1 ) for 28 days. The probiotic feeding in acute and sub-acute toxicity studies showed no mortality or significant abnormalities in rats throughout the experimental period. In week 2 of the acute study, the body weight of the rats showed a significant increase (p < 0.05) compared to the control. By gross and microscopic examination of organs, no evidently significant changes were observed in the morphology of organs. Serum biochemical tests and blood hematology tests also revealed no treatment-related changes. Overall, these data indicated that oral administration of B. amyloliquefaciens HTI-19 up to 1 × 109 CFU·mL−1 for 28 days can be considered safe.